Correlation between changes in placental morphological features with abnormal Doppler flow in pregnancy induced hypertension - Gadhavi, Vijay N.; Gadhavi, Mansi K.; Pandya, Manish (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Placenta is one of the most challenging organs; it is an instrument of transfer of essential elements, i.e. nutrients and oxygen from mother to fetus and waste product of metabolism in reverse manner. Methods: Cases of PIH between 20-36 weeks of gestation will be studied over a peri-od of 2 years having B.P ≥140/90mm Hg and protienuria ≥1+ in this prospective analytical study having color Doppler scanner with PI, RI of umbilical, uterine artery and middle cerebral artery PI along with placental morphological changes are observed. Results: In present study where, placental weight was <300g also has LBW babies born were higher 51(100%). In placental gross examination 58% infarction, 42% calcification and 48% retroplacental were found. among 58 samples with infarction 76%, 42 placentas had calcification 48% and among 49 samples retroplacental clots 61% were belonged to uterine artery PI >1 group. While 78% placental infarction, 57% calcification and 69% retroplacental clots be-longed to uterine artery RI > 0.6 group. Infarction were 77.50%, calcification were same as infarction 77.50% while retroplacental clots 80% in group having MCA PI <1.3 that were higher than group of cases having MCA PI >1.3. Conclusions: In recent years placenta has drawn attention as valuable indicator for maternal and fetal diseases in preeclampsia. Decreased circulation in placenta reflects on its morphological features and these changes causes alterations in Doppler flow velocities of uterine, umbilical and middle cerebral vessels pregnancy induced hyper-tension.